To share or not to share: Malaysian healthcare professionals' views on localized prostate cancer treatment decision making roles - Lee, Yew Kong; Lee, Ping Yein; Cheong, Ai Theng; Ng, Chirk Jenn; Abdullah, Khatijah Lim; Ong, Teng Aik; Abdul Razack, Azad Hassan (Public Library of Science, 2015)
Aim: To explore the views of Malaysian healthcare professionals (HCPs) on stakeholders’ decision making roles in localized prostate cancer (PCa) treatment. Methods: Qualitative interviews and focus groups were conducted with HCPs treating PCa. Data was analysed using a thematic approach. Four in-depth interviews and three focus group discussions were conducted between December 2012 and March 2013 using a topic guide. Interviews were audio-recorded, transcribed verbatim, and analysed thematically. Findings: The participants comprised private urologists (n = 4), government urologists (n = 6), urology trainees (n = 6), government policy maker (n = 1) and oncologists (n = 3). HCP perceptions of the roles of the three parties involved (HCPs, patients, family) included: HCP as the main decision maker, HCP as a guide to patients’ decision making, HCP as a facilitator to family involvement, patients as main decision maker and patient prefers HCP to decide. HCPs preferred to share the decision with patients due to equipoise between prostate treatment options. Family culture was important as family members often decided on the patient’s treatment due to Malaysia’s close-knit family culture. Conclusions: A range of decision making roles were reported by HCPs. It is thus important that stakeholder roles are clarified during PCa treatment decisions. HCPs need to cultivate an awareness of sociocultural norms and family dynamics when supporting non-Western patients in making decisions about PCa.